Lenalidomide in patients with red blood cell transfusion-dependent myelodysplastic syndrome and del(5q): a single-centre "real-world" experience. Issue 11 (2nd November 2015) - Cerqui, Elisa; Pelizzari, Annamaria; Schieppati, Francesca; Borlenghi, Erika; Pagani, Chiara; Bellotti, Daniela; Lamorgese, Cinzia; Boiocchi, Leonardo; Sottini, Alessandra; Imberti, Luisa; Rossi, Giuseppe
Abstract : "Real life" data are needed to complement published trials on the efficacy of lenalidomide in patients with myelodysplastic syndrome (MDS) and del(5q) and on the risk of inducing acute myeloid leukemia (AML) progression. Here, we present results of lenalidomide treatment in a consecutive, population-based series of 21 red blood cell (RBC) transfusion-dependent elderly patients with multiple comorbidities. Of 18 evaluable patients (median follow-up: 22 months), 17 achieved an erythroid hematologic response (HI-E) and 16 an RBC transfusion independence. Cytogenetic response (CyR) rate was 80%, median overall survival was 48 months (range 3–164), and 5-year leukemia-free survival was 84%. Three patients progressed to AML; one, with baseline TP53 mutation, achieved HI-E, partial CyR, and did not progress to AML. Eighteen patients experienced hematological adverse events. Overall, lenalidomide was very effective and well tolerated even in unselected elderly patients with multiple comorbidities and did not appear to increase the risk of AML.